Genome analyses of the sunflower pathogen Plasmopara halstedii provide insights into effector evolution in downy mildews and Phytophthora. (December 2015) - Sharma, Rahul; Xia, Xiaojuan; Cano, Liliana; Evangelisti, Edouard; Kemen, Eric; Judelson, Howard; Oome, Stan; Sambles, Christine; van den Hoogen, D.; Kitner, Miloslav; Klein, Joël; Meijer, Harold; et al.
Abstract Background Downy mildews are the most speciose group of oomycetes and affect crops of great economic importance. So far, there is only a single deeply-sequenced downy mildew genome available, fromHyaloperonospora arabidopsidis . Further genomic resources for downy mildews are required to study their evolution, including pathogenicity effector proteins, such as RxLR effectors.Plasmopara halstedii is a devastating pathogen of sunflower and a potential pathosystem model to study downy mildews, as severalAvr -genes andR -genes have been predicted and unlikeArabidopsis downy mildew, large quantities of almost contamination-free material can be obtained easily. Results Here a high-quality draft genome ofPlasmopara halstedii is reported and analysed with respect to various aspects, including genome organisation, secondary metabolism, effector proteins and comparative genomics with other sequenced oomycetes. Interestingly, the present analyses revealed further variation of the RxLR motif, suggesting an important role of the conservation of the dEER-motif. Orthology analyses revealed the conservation of 28 RxLR-like core effectors amongPhytophthora species. Only six putative RxLR-like effectors were shared by the two sequenced downy mildews, highlighting the fast and largely independent evolution of two of the three major downy mildew lineages. This is seemingly supported by phylogenomic results, in which downy mildews did not appear to be monophyletic. Conclusions The genome resource will be useful for developing markers for monitoring the pathogen population and might provide the basis for new approaches to fightPhytophthora and downy mildew pathogens by targeting core pathogenicity effectors.